Plasma-Generated X-ray Pulses: Betatron Radiation Opportunities at EuPRAXIA@SPARC_LAB - Francesco Stellato; Maria Pia Anania; Antonella Balerna; Simone Botticelli; Marcello Coreno; Gemma Costa; Mario Galletti; Massimo Ferrario; Augusto Marcelli; Velia Minicozzi; Silvia Morante; Riccardo Pompili; et al. (Condensed Matter, 2022)
EuPRAXIA is a leading European project aimed at the development of a dedicated, ground-breaking, ultra-compact accelerator research infrastructure based on novel plasma acceleration concepts and laser technology and on the development of their users’ communities. Within this framework, the Laboratori Nazionali di Frascati (LNF, INFN) will be equipped with a unique combination of an X-band RF LINAC generating high-brightness GeV-range electron beams, a 0.5 PW class laser system and the first fifth-generation free electron laser (FEL) source driven by a plasma-based accelerator, the EuPRAXIA@SPARC_LAB facility. Wiggler-like radiation emitted by electrons accelerated in plasma wakefields gives rise to brilliant, ultra-short X-ray pulses, called betatron radiation. Extensive studies have been performed at the FLAME laser facility at LNF, INFN, where betatron radiation was measured and characterized. The purpose of this paper is to describe the betatron spectrum emitted by particle wakefield acceleration at EuPRAXIA@SPARC_LAB and provide an overview of the foreseen applications of this specific source, thus helping to establish a future user community interested in (possibly coupled) FEL and betatron radiation experiments. In order to provide a quantitative estimate of the expected betatron spectrum and therefore to present suitable applications, we performed simple simulations to determine the spectrum of the betatron radiation emitted at EuPRAXIA@SPARC_LAB. With reference to experiments performed exploiting similar betatron sources, we highlight the opportunities offered by its brilliant femtosecond pulses for ultra-fast X-ray spectroscopy and imaging measurements, but also as an ancillary tool for designing and testing FEL instrumentation and experiments.